Impact of urban–rural resident basic medical insurance on consumption quality of middle-aged and older adult residents: evidence from rural China - Zhou, Yajie; Ping, Junyu (Frontiers in Public Health, 2024)
In the context of the Chinese government's advocacy for "Internal Circulation", ongoing reforms in medical insurance policies raise critical questions about whether the basic medical insurance system can stimulate resident consumption and enhance its quality.Based on five waves of panel data from the China Health and Retirement Longitudinal Survey (CHARLS), this paper analyzes the impact of medical insurance on the consumption scale and structure of middle-aged and elderly rural residents under the difference-in-differences framework. The findings indicate that the Urban-Rural Resident Basic Medical Insurance (URRBMI) effectively stimulates the consumption scale of rural middleaged and elderly individuals, particularly enhancing non-food consumption, development-oriented spending, and hedonic consumption. This, in turn, optimizes the consumption structure and improves overall consumption quality. Notably, URRBMI significantly enhances the consumption scale and structure among rural middle-aged and elderly women, unmarried individuals, and residents in western China. These results suggest that URRBMI plays a crucial role in alleviating consumption inequality within rural areas and across different regions, providing a theoretical foundation for policy-making.